DEVELOPMENT OF A HYBRID POLYMER-BASED MICROFLUIDIC PLATFORM FOR CULTURING HEPATOCYTES TOWARDS LIVER-ON-A-CHIP APPLICATIONS - Kulsharova, Gulsim; Kurmangaliyeva, Akbota; Darbayeva, Elvira; Rojas-Solórzano, Luis; Toxeitova, Galiya (MDPI, 2021)
The drug development process can greatly benefit from liver-on-a-chip platforms aiming to recapitulate the physiology, mechanisms, and functionalities of liver cells in an in vitro environ-ment. The liver is the most important organ in drug metabolism investigation. Here, we report the development of a hybrid cyclic olefin copolymer (COC) and polydimethylsiloxane (PDMS) mi-crofluidic (HCP) platform to culture a Huh7 hepatoma cell line in dynamic conditions towards the development of a liver-on-a-chip system. The microfluidic platform is comprised of a COC bottom layer with a microchannel and PDMS-based flat top layer sandwiched together. The HCP device was applied for culturing Huh7 cells grown on a collagen-coated microchannel. A computational fluid dynamics modeling study was conducted for the HCP device design revealing the presence of air volume fraction in the chamber and methods for optimizing experimental handling of the device. The functionality and metabolic activity of perfusion culture were assessed by the secretion rates of albumin, urea, and cell viability visualization. The HCP device hepatic culture remained functional and intact for 24 h, as assessed by resulting levels of biomarkers similar to published studies on other in vitro and 2D cell models. The present results provide a proof-of-concept demonstration of the hybrid COC–PDMS microfluidic chip for successfully culturing a Huh7 hepatoma cell line, thus paving the path towards developing a liver-on-a-chip platform.
Keywords: Type of access: Open Access; Cyclic olefin copolymer; Hepatocytes; Huh7; Hybrid polymer-based liver-on-a-chip; Liver-on-a-chip; Microfluidic chip; Research Subject Categories::TECHNOLOGY